A Systems study, analysis and design of the Regulatory Services Sub-system of the Local Water Utilities Administration - Dimabuyu, Felinore; Cabida, Tonette; Corpus, Rowena; Dela Cruz, Mimi; Vitriolo, Julito (College of Engineering, 1984)
The group, first, endeavored to look into the total LWUA system and it was only after several data gathering visits to LWUA that the group concentrated the system study in the Regulatory Services. The Regulatory Services is essentially the monitoring and evaluating arm of LWUA with regards the policies and guidelines of the LWUA system to the WDS. The proposed system design is simply a systems and procedures design without any alteration of the organizational structure of both the R/S and LWUA total system. The proposed design aims to improve the implementation, monitoring and evaluation capability of the Regulatory Services (R/S). The implementation of the proposed system would require initially a modicum of manpower increase but from the Benefits-Costs comparison, the potential of the new system design for monitoring, evaluation, implementation and problem-solving efficiency would justify the initial Costs. In the long run, the proposed design would improve financial, technical viability and institutional development of the Water District.